Factors that intervene in the student engagement throughout their learning process, studying the intermediate english level at the Department of Foreign Languages of the University of El Salvador - Guerrero Martínez, Sandra Maribel
Findings on factors affecting student engagement in the University of El Salvador for the students of the first year of Licenciatura in English teaching are presented. Such study was conducted from March to December 2012. The study investigated important details of previous research; this was included in the literature review. It was conducted in a research approach a study based on a qualitative and quantitative approach in which each student responded to a check list about their lives as students; besides, the study also took consideration of an observational guide to get the different behaviors of students in the class. The study attempted to involve all of the students in the sample; however some students did not attended to class during our study.